Modern Architecture in the Design of Syiah Kuala University Student Sports Center - livia aditiya (Universitas Syiah Kuala, 2019)
Syiah Kuala University currently has a Sport Center, but due to the overall lack of maintenance and the lack of facilities that support activities so that only a few activities can be accommodated, making this building ineffective and cannot function optimally as it should.Therefore, in this writing, the aim is to create or design a Sport Center of Syiah Kuala University design that is able to facilitate activities in Unsyiah. This design will take the theme of Modern Architecture.The use of the theme of modern architecture itself is motivated by the function of the Sport Center to be planned as the Sport activity. Modern architectural themes are expected to be able to provide characteristics that are suitable for both space and users.Modern architecture is a term given to buildings that have characteristic styles that prioritize simplicity of form and remove all ornaments. Based on the book